Pain Control by Co-adaptive Learning in a Brain-Machine Interface - Zhang, Suyi; Yoshida, Wako; Mano, Hiroaki; Yanagisawa, Takufumi; Mancini, Flavia; Shibata, Kazuhisa; Kawato, Mitsuo; Seymour, Ben (Current biology, 2020)
Innovation in the field of brain-machine interfacing offers a new approach to managing human pain. In principle, it should be possible to use brain activity to directly control a therapeutic intervention in an interactive, closed-loop manner. But this raises the question as to whether the brain activity changes as a function of this interaction. Here, we used real-time decoded functional MRI responses from the insula cortex as input into a closed-loop control system aimed at reducing pain and looked for co-adaptive neural and behavioral changes. As subjects engaged in active cognitive strategies orientated toward the control system, such as trying to enhance their brain activity, pain encoding in the insula was paradoxically degraded. From a mechanistic perspective, we found that cognitive engagement was accompanied by activation of the endogenous pain modulation system, manifested by the attentional modulation of pain ratings and enhanced pain responses in pregenual anterior cingulate cortex and periaqueductal gray. Further behavioral evidence of endogenous modulation was confirmed in a second experiment using an EEG-based closed-loop system. Overall, the results show that implementing brain-machine control systems for pain induces a parallel set of co-adaptive changes in the brain, and this can interfere with the brain signals and behavior under control. More generally, this illustrates a fundamental challenge of brain decoding applications—that the brain inherently adapts to being decoded, especially as a result of cognitive processes related to learning and cooperation. Understanding the nature of these co-adaptive processes informs strategies to mitigate or exploit them. [Display omitted] •Adaptive control system can use brain activity to guide interventions to reduce pain•The brain changes when it knows it is being decoded•These co-adaptive changes can disrupt decoded signals and modulate pain perception Zhang et al. use real-time decoded fMRI responses from the insula cortex as input into a closed-loop control system aimed at reducing pain. They find that brain-machine interface control systems for pain induces a parallel set of co-adaptive changes in brain and behavior, illustrating the brain’s ability to adapt to being decoded through learning.